Effect of the Improvement of Microbiological and Toxicological Qualities Regarding Ochratoxin A Producing Fungi Using of Lactic Acid Bacteria Strains on the Sensorial Quality of Derived Beverage - Guézéré Corinne Beugre; Adobi Christian Kadjo; Konan Mathurin Yao; Koumba Maï Kone; Isabelle Piro-Metayer; Charlie Poss; Noël Durand; Angélique Fontana; Tagro Simplice Guehi (Current Perspectives in Agriculture and Food Science Vol. 5, 2023)
Various biological trials were currently made to improve the microbiological quality and safety of the coffee cherries without effect on the sensorial quality of drink produced thereof. This study investigated the effect of the inhibition of growth and reduction the production of ochratoxin A (OTA) of Aspergillus carbonarius using of Lactic Acid Bacteria (LAB) strains on the sensory profile of derived beverage. Emerging processing methods have been applied in coffee bean processing for improved sensory quality. The processes focus on optimizing the fermentation process of the coffee cherries and beans. This involves various pathways, including the formation of volatiles, flavor precursors and organic acids and the reduction in the concentrations of bioactive compounds. Nine samples of 1-5 kg fresh coffee cherries (robusta Coffea canephora) were harvested directly from coffee trees and seven samples of dry cherries stocks were collected from Akoupé, Daloa, Man; 3 main coffee producing region of Côte d’Ivoire in January 2018. LAB were isolated from fresh coffee cherries while mold strains were from both fresh and dry coffee cherry. Prior to assessing their impact on beverage sensory quality, certain LAB strains were examined for their ability to remove OTA during primary postharvest processing of coffee cherries and for their inhibitory activity against mold growth in vitro. Mold strains’ capacity to produce OTA is investigated using Cazapeck Yeast medium that is both solid (CYA) and liquid (CYB). Sixteen LAB isolates presented common morphological and biochemical characteristics of LAB (results not showed). Molecular identification showed that eleven isolates (75 %) were Lactobacillus plantarum, 2 isolates were Weissella paramesenteroides (12.5 %), 1 isolate was W. confusa (6.3 %) and 1 unidentified isolate. About 34 fungal isolates belonging to Aspergillus and Penicillium genus were studied for their OTA production using the agar plug technique and HPLC-FD. Five A. carbonarius strains were capable of OTA production between 15.9 and 83mg.kg-1.Out of seven isolates of Lactobacillus plantarum, two were successful in inhibition of mycelial growthproduced fungicidal activity; five were successful in retarding it produced fungistatical activity All of L. plantarum isolates exhibited OTA reduction ability at about 99 %. The inoculation of L. plantarum LAB D12 and LAB D13 certainly had an impact on the production of VOCs involved in beverrages sensory qualities. According to Pereira et al. [1], the volatile organic compounds (VOCs) produced by LAB included ester, alcohol, alkane, acid, hydrocarbon, ether and nitrogen-containing. This study highlighted that LAB are very promising biological candidates for reduction of mold contamination and removal OTA from coffee cherry during primary postharvest processing.